Pharmacological screening of Eryngium foetidum Linn – A Review - Galamula Hewage Tharuka Kanchana Hemachandra; Sinnadurai Thuvaragan; Vinotha Sanmugarajah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Eryngium foetidum L. (Family Apiaceae) is a biennial herb, and it is used as a culinary herb and spice across the different countries of the world, including Sri Lanka, India, Bangladesh, Malaysia, Singapore, etc. due to its high aroma quality. Also, it is used to treat several ailments, such as respiratory diseases, gastrointestinal ailments, and skin diseases among different indigenous populations for its medicinal properties. Based on ethnomedical evidence, many studies have been conducted to identify the phytoconstituents, underlying mechanisms, and related pharmacological effects of different parts of this plant. This study reviewed the current state of findings related to the Pharmacological activities of E. foetidum. Based on this review, this plant is widely used for ethnomedical and culinary purposes. Pharmacological screening of the plant revealed that it had different activities such as anti-inflammatory, antioxidant, antimicrobial, anthelminthic, anticonvulsant, anticancer, antidiabetic, antimalarial, larvicidal, and hepatoprotective activities. This review further promised that potential new chemical entities could be elicited from the phytoconstituents of E. foetidum.